Macondo, a representação da decolonialidade latino-americana em Cien años de soledad [1967] (1987-2007) - Cavalcante, Marcia Alves dos Santos (2024)
The work One Hundred Years of Solitude (1967) by Gabriel García Márquez, Colombian writer, translator, journalist, editor and political activist, is analyzed with the aim of revealing the contributions of the novel to the understanding of aspects of Latin American identity. It reveals how the author, following the perspective in force at the time, highlights an aesthetic of appreciation of Latin American cultural roots in opposition to the Cartesian rationalism that underpins most of the literature related to such topics. In this sense, we consider that Márquez incorporates elements of subjectivity as inherent characteristics of human actions that result in historical trajectories capable of, in their own way, facing the constant subjugation of the Latin American being. In other words, the decoloniality that is revealed in the magic of the hybrid or native populations of the region. Based on everyday scenes from both the fictional city of Macondo and its inhabitants, García Márquez recounts historical episodes that address the process of colonization and, consequently, relations of subordination, explaining exploitation and epistemic violence – coercive forms to which meanings are attributed to legitimize agendas that guarantee positions of power – a reality not only of Colombian society, but of Latin America as a whole. But, beyond that, his work reveals the understanding of these populations regarding said violence, based on the particular way of facing the historical evolution rooted in their cultures